2018
DOI: 10.1177/0013916518804017
|View full text |Cite
|
Sign up to set email alerts
|

Visitor Attention in Exhibitions: The Impact of Exhibit Objects’ Ordinal Position, Relative Size, and Proximity to Larger Objects

Abstract: The main aim of the present study was to explore the impact of three stimulus-related variables-that is, ordinal position of viewing, relative size of exhibit objects, and proximity to larger sized objects-on visitor attention and interest in exhibitions. A field experiment that utilized timing and tracking through unobtrusive observation, as well as a questionnaire, was conducted with 120 participants in one control and three experimental conditions. The results suggest that (a) visitor attention declines acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Furthermore, the mean AHT associated with DE2 (involving three-dimensionality) was found to be greater than that for DE1 (involving size), suggesting that three-dimensionality seems to be a stronger salience parameter than size. Thus, the results of the present digital exhibition study were congruent with previous reports involving the greater attention-holding capability of salient exhibit objects (associated with higher value ratio) in physical exhibitions (Bitgood and Patterson 1987;Bitgood et al 1986;Bitgood, Patterson, and Benefield 1988;Marcellini and Jenssen 1988;Peart 1984;Turgay Zıraman and Imamoğlu 2020).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the mean AHT associated with DE2 (involving three-dimensionality) was found to be greater than that for DE1 (involving size), suggesting that three-dimensionality seems to be a stronger salience parameter than size. Thus, the results of the present digital exhibition study were congruent with previous reports involving the greater attention-holding capability of salient exhibit objects (associated with higher value ratio) in physical exhibitions (Bitgood and Patterson 1987;Bitgood et al 1986;Bitgood, Patterson, and Benefield 1988;Marcellini and Jenssen 1988;Peart 1984;Turgay Zıraman and Imamoğlu 2020).…”
Section: Discussionsupporting
confidence: 92%
“…As the first independent variable addressed in the present study, ordinal position of exhibit objects was previously shown to influence attention distribution schemes. For example, the amount of visitor attention allocated to individual exhibit objects tends to decrease as the visitors proceed toward the end of exhibitions, due to factors such as fatigue or object satiation (Bitgood 2002(Bitgood , 2009(Bitgood , 2013Bitgood and Patterson 1987;Johnston 1998;Melton 1935;Robinson 1928;Turgay Zıraman and Imamoğlu 2020). Turgay Zıraman and Imamoğlu (2020) also reported that the ordinal position effect seemed to be independent of the exhibit objects' salience levels involving size.…”
Section: Visitor Attention and The General Value Principlementioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research has demonstrated the impact of an exhibit's presentation context on visitors' behavior. Besides its overall spatial position in a gallery (Eghbal‐Azar, Merkt, Bahnmueller, & Schwan, 2016; Turgay Zıraman & Imamoğlu, 2018), size and attractivity of other exhibits in the immediate surrounding may strongly influence how much attention visitors pay to a particular authentic object (Turgay Zıraman & Imamoğlu, 2018). More importantly, providing labels and explaining texts has been shown to prolong the visitors' inspection time, guide their attention, and foster a deeper understanding of an object (Schwan, Dutz, & Dreger, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, they may encounter text placards or recorded voiceovers that provide information about the exhibit, but they may not even read or listen to the information. They also are free to select a subset of available information they found most salient from the whole exhibit (Turgay Zıraman & Imamoğlu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%